Impact of manganese diffusion into non-oriented electrical steel on power loss and permeability at different temperatures - Elgamli, Elmazeg; Anayi, Fatih; Shouran, Mokhtar (Frontiers in Materials, 2023)
Minimising power losses and their consequences is a significant matter in electrical steel applications. Increasing the resistivity of the steel strips has been confirmed as a successful method to overcome the problem of power losses. To increase the resistivity of the strip, different effective methods have been proposed and tested. In this work, a new material has been proposed to achieve the objective of increasing the resistivity of the steel samples by adding Manganese (IV) oxide based on a diffusion technique. The steel samples are to be coated with the proposed Manganese oxide. This should guarantee an increase in the resistivity of the sample, which in turn reduces the power losses caused by the eddy current. The samples tested were of non-oriented electrical steels containing 2.4wt% Si-Fe (with a thickness of 0.305 mm*300 mm*30mm). It was measured for losses and permeability before and after treatment by a Single Strip Tester (SST) at 0.5 T to 1.7 T using an AC magnetic properties measurement system under controlled sinusoidal at different frequencies. The obtained results revealed that the depth of Manganese oxide diffusion is inversely proportional to the increase in the temperature. It was demonstrated that the best amount of diffusion of the element into the strips was achieved at 525 °C, which was 60 weight % in comparison with 700 °C which was 20 wt %. Likewise, at 800 °C it was 7 wt %. However, the depth of diffusion of the manganese was the same at those tested temperatures, which were equal to 200 µ m deep on each of the side strips. The diffusion of the material was investigated using Scanning Electron Microscopy (SEM) coupled with Energy Dispersive X-ray Spectroscopy (EDS). Furthermore, from the results, it was concluded that the power losses in the coating samples were improved by 9% as compared with uncoated samples